Correction to: Bioengineering potato plants to produce benzylglucosinolate for improved broad-spectrum pest and disease resistance - González Romero, M.E.; Rivera, C.; Cancino, K.; Geu-Flores, F.; Cosio, E.G.; Ghislain, M.; Halkier, B.A. (Springer, 2021)
In the above mentioned publication, a third affiliation was erroneously indicated for M. E. González-Romero where it should have been two. The original article has been corrected and the correct affiliations are also published here.